Akutní nekróza jícnu - Husová, L; Múcková, K; Kroupa, R; Dastych, M; Senkyrík, M (Casopis lekaru ceskych, 2005)
The case of acute oesophageal necrosis in 56-year-old patient with tumor dissemination is presented. Acute endoscopy was performed after several hours lasting haematemesis and melena. Endoscopy revealed acute oesophageal necrosis in more than 2/3 of the oesophagus. Patient was treated with proton pump blockers and the total parenteral sustenance was introduced. Three days after the hospital admission the patient died in the septical metabolic disorder resulting from a disseminated spinocellular carcinoma of cervix uteri. Autopsy confirmed necrosis of oesophageal mucosa penetrating into the muscularis mucosae. Acute oesophageal necrosis is a rare disease, which is characteristic by the endoscopic finding of "black oesophagus", histological image of mucous membrane necrosis and by unknown aetiology. The article gives an overview of contemporary knowledge on the clinical, endoscopic and histologic images. The finding of "black oesophagus", which has been reported by several endoscopic units, has highly heterogeneous origin and it represents 0.0125 % (Moreto) till 0.28 % (Augusto) of cases. Our department has recorded 2 cases from 24271 of endoscopies performed in the last 8 years.
Keywords: Esophagus; Humans; střevní nádory; lidé středního věku; nekróza; Duodenum; Female; nádory děložního čípku; lidé; Intestinal Neoplasms; duodenum; ženské pohlaví; Middle Aged; ezofágus; Uterine Cervical Neoplasms; spinocelulární karcinom; Carcinoma, Squamous Cell; Acute Disease; Necrosis; akutní nemoc